Resilience – and collapse – of local food systems in conflict affected areas; reflections from Burkina Faso - Béné, Christophe; d'Hôtel, Elodie Maître; Pelloquin, Raphaël; Badaoui, Outman; Garba, Faroukou; Sankima, Jocelyne W. (Elsevier, 2024)
Armed conflicts are among the major disruptions affecting local food systems in low- and middle-income countries, having devastating effects on populations’ food security. The understanding of the mechanisms linking conflicts to food insecurity is limited, however, by a lack of data on how these conflicts affect the different actors of local food systems. In this study, we aim to address this gap, using empirical data from the northeast region of Burkina Faso where an active conflict is occurring. The objective is to document and analyze the impacts of that conflict on the functioning of the local food system and more specifically on the resilience of the traders that operate from Sebba, the capital of the Yagha province. The analysis reveals, first, the magnitude of the disruption. On average, these local food traders experienced a 40%-50% contraction in their activities compared to the situation prior to the conflict. Not all operators are affected with the same intensity, however. Transporters appeared to be impacted more severely than retailers/vendors. Econometric models are then used to explore the socio-economic characteristics of these different actors. The analysis shows that, contrarily to what is often observed with farmers, the level of assets did not seem to contribute significantly to traders’ resilience. Instead, having recently relocated to Sebba appears more important to ensure the level of adaptability needed to respond to the rapidly deteriorating situation. The analysis also reveals that the resilience of the “positive deviants” (those operators who did better than the rest of the group) materialized essentially through their capacity to buffer more effectively shocks’ impacts but it did not spare them from facing drastic contractions in their trade business. Eventually, the resilience of those positive deviants was not sufficient to maintain the resilience of the whole system. It ensues a catastrophic drop in the quantity of food traded (up to 50% for certain products), leading to the collapse of the system and a 10-fold increase in the food insecurity of the local population. The paper concludes by weighing the usefulness of the concept of resilience in the context of severe disruptions of the food systems (such as armed conflicts), emphasizes the risk that an unconditional promotion/adoption of that concept may reduce our ability to anticipate or even to envision collapse scenarios. On the brighter side, our analysis demonstrates that collecting specific information about the food system operators can help predict, and possibly prevent, such collapses.